FACTORS INFLUENCING PURCHASE INTENTION OF IMPORTED FOOD IN BATAM CITY - Erilia Kesumahati; Regina Regina; Andina Fasha (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the factors influencing consumers’ purchase intention toward imported food products in Batam City, with a particular focus on the role of trust. The background of this research is the increasing circulation of imported food products in Batam as a free trade zone, which intensifies competition with local products and raises concerns related to consumer trust. This study addresses the problem of how attitude, brand image, country of origin, price, and product quality influence trust and how trust affects purchase intention. A quantitative research approach was employed by distributing structured questionnaires to 363 respondents who had purchased imported food products in Batam City. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results indicate that attitude, brand image, country of origin, price, and product quality have a positive and significant effect on trust. Among these factors, brand image is identified as the most influential in building consumer trust. Furthermore, trust has a strong and significant effect on purchase intention toward imported food products. These findings emphasize the importance of trust in shaping consumers’ purchasing decisions and provide practical insights for businesses in strengthening trust to enhance purchase intention in the imported food market.